Neuron to Oligodendrocyte Precursor Cell Synapses: Protagonists in Oligodendrocyte Development and Myelination, and Targets for Therapeutics - Moura, Daniela M. S.; Brennan, Emma J.; Brock, Robert; Cocas, Laura A. (Frontiers in Neuroscience, 2022)
The development of neuronal circuitry required for cognition, complex motor behaviors, and sensory integration requires myelination. The role of glial cells such as astrocytes and microglia in shaping synapses and circuits have been covered in other reviews in this journal and elsewhere. This review summarizes the role of another glial cell type, oligodendrocytes, in shaping synapse formation, neuronal circuit development, and myelination in both normal development and in demyelinating disease. Oligodendrocytes ensheath and insulate neuronal axons with myelin, and this facilitates fast conduction of electrical nerve impulses via saltatory conduction. Oligodendrocytes also proliferate during postnatal development, and defects in their maturation have been linked to abnormal myelination. Myelination also regulates the timing of activity in neural circuits and is important for maintaining the health of axons and providing nutritional support. Recent studies have shown that dysfunction in oligodendrocyte development and in myelination can contribute to defects in neuronal synapse formation and circuit development. We discuss glutamatergic and GABAergic receptors and voltage gated ion channel expression and function in oligodendrocyte development and myelination. We explain the role of excitatory and inhibitory neurotransmission on oligodendrocyte proliferation, migration, differentiation, and myelination. We then focus on how our understanding of the synaptic connectivity between neurons and OPCs can inform future therapeutics in demyelinating disease, and discuss gaps in the literature that would inform new therapies for remyelination.